2017
DOI: 10.1093/toxsci/kfx123
|View full text |Cite
|
Sign up to set email alerts
|

From the Cover: Exposure to an Environmentally Relevant Mixture of Brominated Flame Retardants Decreased p-β-Cateninser675 Expression and Its Interaction With E-Cadherin in the Mammary Glands of Lactating Rats

Abstract: Proper mammary gland development and function require precise hormonal regulation and bidirectional cross talk between cells provided by means of paracrine factors as well as intercellular junctions; exposure to environmental endocrine disruptors can disturb these processes. Exposure to one such family of chemicals, the brominated flame retardants (BFRs), is ubiquitous. Here, we tested the hypothesis that BFR exposures disrupt signaling pathways and intercellular junctions that control mammary gland developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In breast cancer cell lines, β-catenin is mainly localized on the cell membrane of MCF-7 cells, while in SKBR3 cells, it is mainly localized in the cytoplasm and nucleus [ 38 ]. Cell membrane expression of pSer675-β-catenin was also observed in liver cancer cells and rat mammary gland epithelial cells [ 39 , 40 ]. We are also concerned about the result of a study showing that the expression of downstream target genes of β-catenin is not completely dependent on nuclear β-catenin [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer cell lines, β-catenin is mainly localized on the cell membrane of MCF-7 cells, while in SKBR3 cells, it is mainly localized in the cytoplasm and nucleus [ 38 ]. Cell membrane expression of pSer675-β-catenin was also observed in liver cancer cells and rat mammary gland epithelial cells [ 39 , 40 ]. We are also concerned about the result of a study showing that the expression of downstream target genes of β-catenin is not completely dependent on nuclear β-catenin [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies were identified in which the experimental animals were exposed to PBDEs together with other BFRs and/or other POPs (Allais et al., 2020 ; Berger et al., 2014 ; Berntsen et al., 2021 ; Dianati et al., 2017 ; Ernest et al., 2012 ; Gouesse et al., 2021 ; Hansen et al., 2019 ; Johanson et al., 2020 ; Khezri et al., 2017 ; Lefevre et al., 2016 ; Mailloux et al., 2014 , 2015 ; Myhre et al., 2021 ; Tung et al., 2016 , 2017 ). The CONTAM Panel did not consider these studies informative for the hazard characterisation of PBDEs and thus these studies were not considered in this Opinion.…”
Section: Assessmentmentioning
confidence: 99%
“…Several studies were identified in which the animals were exposed to HBCDDs together with other BFRs and/or other POPs (Ernest et al, 2012;Berger et al, 2014;Lefevre et al, 2016;Dianati et al, 2017;Tung et al, 2016Tung et al, , 2017Allais et al, 2020). The CONTAM Panel did not consider these studies informative for the hazard characterisation of HBCDDs and thus were not considered in this Opinion.…”
Section: Toxicity In Experimental Animalsmentioning
confidence: 99%